Co-ordination of Forestry and Mineral Development in Forest Areas - Datta, N.R. (Journal of Soil and Water Conservation, 2022)
It is a well known fact that the mining activity, especially by open-cast method in slopy forest areas, accelerates soil erosion and adversely affects the forestry. Most of our major mineral deposits, specially those of Iron ores, Manganese ores, Bauxite, Chromite, Mica etc. are located in Reserve Forests. The mines of these minerals are mostly confined to seven states namely; Andhra Pradesh, Madhya Pradesh, Bihar, Maharashtra, Mysore, Orissa and Rajasthan. The statewise distribution of mining leases and mines as on 1.1.60 is indicated in table No. 1. With the exception of Jharia and Raniganj coal fields, the major Indian coal fields viz., East and West Bokaro, North and South Karanpura and Ramgarh in Bihar, Chirimiri, Bishrampur, Sohagpur, Sonhat, Pench-Kanhan and Tawa-valley coal fields in M.P. are either wholly or partly occupying forest areas. Though the entire mica belt of Bihar, especially the portion lying in Hazari-bagli and Gaya districts, is situated in the Reserve Forest, the mineral development activities in these areas mostly being of underground mining nature, the forest is not severely affected, as compared to the areas where the development activities are mostly of opencast mining.